Experimentos em espaços não formais de aprendizagem na aprendizagem de Física - Lindaura Alves Coelho (2016)
In the present paper I will bring an educational intervention proposal up as a motivational strategy for Physics teaching. This proposal encourages the development of activities and the mediation of Physics experiments by visitors outside the school environment. The use of information technology in the research and selection of the experiments, the construction of the instruments and the exposition mediated by students were selected as motivational resources to the process, along with the interaction and the active participation of the students. This report summarizes the performance of a Physics experiments exposition, which was mediated by a group of 11th grade students from Juscelino Kubitschek de Oliveira State High School. The exposition was showed in the Ecological Station of Federal University of Minas Gerais (UFMG). The main validity criteria of the proposal included the students motivation during the process and the interaction among the subjects and between the students and the visitors, the space and the exposition. We concluded that the students acquired responsibility, autonomy, creativity, cooperation and autoregulation throughout the development of the exposition. We also developed a textbook as a final product for Physics teachers (Appendix B) containing instructions to replicate the present proposal and the Physics experiments step by step.